Heat and Moisture Transfer in a Two-Layer Building Wall at Slow Harmonic Changes of Thermo-Humiditive Environment Parameters Based on The theory of Thermodiffusion in Solids - Dudziak, W.; Uklejewski, R. (Engineering Transactions, 1991)
In order to describe the thermo-humiditive processes occurring in external building walls, the theory of thermodiffusion in elastic solids is used. This theory allows to take into account the internal coupling between the processes of heat conduction and moisture transfer, as well as it mak.es it possible to determine the stresses during these processes in the wall material. The solutions of the equations describing the process of heat and moisture transfer in a two-layer (and, in general, n-layer) building wall at slow harmonic changes of thermo-humiditive environment parameters are presented. The solutions obtained are of importance for thermo-humiditive design of building walls; the mean month’s values of external climate parameters are assumed to vary sinusoidally during the year. The method of solution, as well as some notions, are based on the theory of electric transmission lines.